Answer:
nth term of geometric sequence = a(n) =
![(3/4)(4/3)^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/6k2w6aza75gtb4r2umi61v1xgv5pgncdip.png)
Explanation:
nth term of geometric sequence = a(n)
nth term of geometric sequence = a(n) =
![ar^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bdw4zdks21thsa2i9vpmxk85fgto4xjbvg.png)
Where,
a = first term
r = common ratio
n = number of term
So,
GP: 3/4, 1, 4/3, 16/9
a = 3/4
r = 1 / [3/4] = 4/3
n = n
nth term of geometric sequence = a(n) =
![ar^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bdw4zdks21thsa2i9vpmxk85fgto4xjbvg.png)
nth term of geometric sequence = a(n) =
![(3/4)(4/3)^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/6k2w6aza75gtb4r2umi61v1xgv5pgncdip.png)